Deconstructing Social Work in Africa: An autoethnographic approach (Journal of Comparative Social Work, 2025)
In the dominant debate, dialogue and literature, there is an assumption that Africa had no form of social work before colonisation. In this article, we deal with the historical question pertaining to the existence of social work in Africa, and deconstruct the term ‘social work’, its origin and meaning in an African context. We employ an autoethnographic approach to describe the knowledge and skills known as social work in African communities using Indigenous Knowledge. We conclude that the Western epistemological paradigm facilitated the idea that social work was non-existent in the pre-colonial era, which distorted and distracted knowledge and skills construction in post-modernism theory and practice